2021
DOI: 10.1182/hematology.2021000239
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong TKI therapy: how to manage cardiovascular and other risks

Abstract: Beginning with imatinib and now spanning 6 oral, highly active, and mostly safe agents, the development of specific targeted therapy for patients with chronic myeloid leukemia (CML) has created a new world featuring chronic maintenance chemotherapy for all treated as such, treatment-free remission, and functional cure after prolonged deep remission in a subset. As a result comes a necessary shift in focus from acute to chronic toxicity, increasing attention to patient comorbidities, and critical thinking aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Finally, a potential strategy to reduce VAE risk among patients with CML could be the discontinuation of TKI treatment [ 35 ]. The global time of TKI treatment is an important variable when considering if a patient is eligible for TKI discontinuation, as is the duration of a deep molecular response, both associated with a higher probability of treatment-free remission [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a potential strategy to reduce VAE risk among patients with CML could be the discontinuation of TKI treatment [ 35 ]. The global time of TKI treatment is an important variable when considering if a patient is eligible for TKI discontinuation, as is the duration of a deep molecular response, both associated with a higher probability of treatment-free remission [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of chronic myeloid leukaemia (CML) has been revolutionised with the introduction of oral tyrosine kinase inhibitors (TKIs). It should be remembered that following approval of TKIs for the treatment of CML, the overall survival of these patients improved to 70% [ 14 ]. Imatinib (a first-generation inhibitor) can reduce serum levels of proatherogenic LDL and can normalise plasma lipid levels in hypercholesterolemic and hypertriglyceridemic patients [ 15 ].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…RATIFY (NCT00651261), a phase III trial, showed that MDS addition to chemotherapy improves survival in FLT3-mutated patients (Stone et al, 2017). Although TKI first-line therapy is used for myelosuppression to induce a hematological response, several side effects like liver dysfunction, edema, fluid retention, fatigue, and gastrointestinal symptoms (Guilhot et al, 2012;Qosa et al, 2018;Mauro, 2021) might occur. On the other hand, chemotherapy usually induces serious side effects that augment in combination with other drugs by becoming acute.…”
Section: Introductionmentioning
confidence: 99%